Pathways of cellular internalisation of liposomes delivered siRNA and effects on siRNA engagement with target mRNA and silencing in cancer cells - Alshehri, Abdullah Ali; Grabowska, Anna M.; Stolnik, Snow (Nature Publishing Group, 2018)
Design of an efficient delivery system is a generally recognised bottleneck in translation of siRNA technology into clinic. Despite research efforts, cellular processes that determine efficiency of siRNA silencing achieved by different delivery formulations remain unclear. Here, we investigated the mechanism(s) of cellular internalisation of a model siRNA-loaded liposome system in a correlation to the engagement of delivered siRNA with its target and consequent silencing by adopting siRNA molecular beacon technology. Probing of cellular internalisation pathways by a panel of pharmacological inhibitors indicated that clathrin-mediated (dynamin-dependent) endocytosis, macropinocytosis (dynamine independent), and cell membrane cholesterol dependent process(es) (clathrin and caveolea-independent) all play a role in the siRNA-liposomes internalization. The inhibition of either of these entry routes was, in general, mirrored by a reduction in the level of siRNA engagement with its target mRNA, as well as in a reduction of the target gene silencing. A dramatic increase in siRNA engagement with its target RNA was observed on disruption of endosomal membrane (by chloroquine), accompanied with an increased silencing. The work thus illustrates that employing molecular beacon siRNA technology one can start to assess the target RNA engagement – a stage between initial cellular internalization and final gene silencing of siRNA delivery systems.